THREE DIMENSION IMAGING OF VP STRUCTURE IN WESTERN JAVA AND SUNDA STRAIT REGION USING SEISMIC TOMOGRAPHY - PRIA SAKTI (NIM : 22410008); Pembimbing : Dr. Andri Dian Nugraha, ARTADI
We have conducted seismic tomographic inversion to obtain a P-wave seismic velocity structure beneath the Sunda Strait and West Java regions, Indonesia. The Sunda Strait is located in a complex geological system i.e. in the transition from the oblique subduction beneath Sumatera to the nearly perpendicular subduction below Java. The Krakatau active volcano is located in the Sunda Strait. In this study we have used selected P-wave arrival times from the data catalogs of the SeiscomP-BMKG network (from 2009 to 2011) and the BMKG region II network (from 1992 to 1999) compiled by Badan Meteorologi, Klimatologi dan Geofisika (BMKG), Indonesia. In total, there are 1,598 local earthquakes and 10366 P-wave phases from 25 seismographic sations that have been used for the tomographic inversion. We have also relocated the hypocetner locations along with velocity inversions simultanously. The results from this research depict some prominent geological features that include: 1) a low velocity anomaly beneath north of the Ujung Kulon region, wich coincides with low gravity anomaly resulting from a previous study, (2) a low velocity anomalies extending from Pelabuhan Ratu towards Jakarta with a strike of SW-NE, and (4) a low velocity anomaly in the offshore of Pelabuhan Ratu that may be correlated with the continuation of the Cimandiri fault zone.